DETERMINAN PENGHINDARAN PAJAK DENGAN KOMISARIS INDEPENDEN SEBAGAI PEMODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Wicaksana, Satya Adi; Djaddang, Syahril; Darmansyah, Darmansyah (Kinerja, 2021)
The study aimed to test the effect of leverage, company size, inventory intensity and liquidity on tax avoidance.In addition, this study also aims to test the influence of independent commissioners who act as moderation. This study was conducted by moderate regression analysis method with sample selection method that is purposive sampling with a sample of 21 manufacturing sector companies during the period 2015-2019.The results showed that leverage positively affects tax avoidance and liquidity negatively affects tax avoidance,while the size of companies and inventory intensity have no influence on tax avoidance.In addition, independent commissioners as moderation strengthen the influence of leverage on tax avoidance.